Anti-Oxidants in Agriculture - Veres, Zsuzsanna; Fári, Gábor Miklós (Acta Agraria Debreceniensis, 2004)
Today’s programmes aiming at enhancement of fruit and vegetable consumption have been intensified. In the unanimous view of experts, different health problems, such as those of the immune system, inflammations, and even certain cancerous diseases can be prevented and/or cured with regular consumption of fresh (raw) fruit and vegetables. It is well-known fact that among the biologically valuable components, antioxidant compounds – C- and E vitamins, as well as carotinoides – play an important role. In this field, Hungary can expect success in the future since it has excellent plant genetic stock. Regretfully, national data banks regarding cultivation technology, cultivation areas or varieties for fruits and vegetables and their antioxidant contents do not exist in Hungary. Nevertheless, in connection with the so-called “Hungaricums” its existence would be of urgent necessity. Such excellent Hungarian products are – among others – a lot of sour cherry varietiles, the Szeged green pepper and the Makó onion. They enjoy high priority as “Hungaricums” even in the European Union and such activities that support these kinds of products should be enhanced by intense and consequent research work, which may prove their role as functional foods. Presently’ the USA leads in the research of antioxidant compounds of sour cherry, and so far 17 of these compounds have been found partly in Hungarian varieties. Similar research on green, and ‘pritamin’ peppers have not gone so far since they were limited only for seasoning paprika. In Hungary, studies on onion and garlic have not been performed. It should be mentioned that due to the continental climate, these products may be cultivated, consumed or processed only in a limited period. Taking this into consideration, processing and conserving methods are needed which make the consumption of these fruit and vegetables as functional food possible year-round. Scientific establishment of this set of questions is of current concern, because consumption of these products could have an important role in improving the health status of the Hungarian population in the future.